Managing surgical & perioperative practice. The operating room of the future. - Mailhot CB (Nursing Management)
As more and more care moves to the home setting, the ability to undergo a surgical procedure from the comfort of your own home may not be that far away. As for the operating room itself patient care will be radically different than it has been in the past. Radiologists, assisted by computers and robots, may be performing procedures on patients 'anesthetized' by acupuncture, therapeutic touch and aromatherapy in a totally bloodless environment.